The development of digital television in Greece - Papathanassopoulos, Stylianos (Javnost (Ljubljana), 2007)
The development of digital television in Greece is in its infancy. In effect, there is no digital cable TV, while the public broadcaster, ERT, has only recently started digital transmissions on the terrestrial frequencies. On the contrary, digital satellite television has presented some development, but this is due to the only pay-TV operator in Greece, Nova - after a wounded digital war with an early competitor, Alpha Digital. However, total pay-TV penetration, both analogue and digital, is less than nine per cent of TV households, one of the lowest pay-TV penetration rates in Europe. This paper will try to discuss the development of digital television in Greece. It will trace the players, the economics and the politics associated with this new television medium, and it will argue that the domestic market, due to its size and peculiarities, is difficult to create the needed economies of scale of the development of digital television.
Keywords: Grčija; Greece; management; digitalne komunikacije; digital television; digitalna televizija; kabelska televizija; razvojna strategija; organizacija; organization; dostopnost